2015
DOI: 10.1109/ted.2015.2470235
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Study of the Impact of Quantum Confinement on the Electrostatically Driven Performance of n-type Nanowire Transistors

Abstract: Abstract-In this paper, we have studied the impact of quantum confinement on the performance of n-type silicon nanowire transistors (NWTs) for application in advanced CMOS technologies. The 3-D drift-diffusion simulations based on the density gradient approach that has been calibrated with respect to the solution of the Schrödinger equation in 2-D cross sections along the direction of the transport are presented. The simulated NWTs have cross sections and dimensional characteristics representative of the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…In our recent publication [27], we reported results for the NWTs with the <110> crystal orientation and similar cross sectional shapes as discussed above but with the 10 times bigger cross sectional area -14 π (44 nm 2 ). In this subsection we expand the already published study by comparing not only the wires with the <110> crystal orientation but also with the <100> channel direction.…”
Section: B Nanowire With a Different Area Of The Cross-sectionmentioning
confidence: 55%
“…In our recent publication [27], we reported results for the NWTs with the <110> crystal orientation and similar cross sectional shapes as discussed above but with the 10 times bigger cross sectional area -14 π (44 nm 2 ). In this subsection we expand the already published study by comparing not only the wires with the <110> crystal orientation but also with the <100> channel direction.…”
Section: B Nanowire With a Different Area Of The Cross-sectionmentioning
confidence: 55%
“…The PS quantum corrections offer a precise charge distribution within the simulated NWTs' channel [5]. And Figure 3 gives the Phi ovals represented on a two-dimensional cross-section at the center of the gate.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the literature indicates that the nanowires' cross-sectional shape strongly affects NWTs' gate capacitance and mobile charge [5][6][7]. As a case in point, for an NWT characterized by <110> channel orientation, as well as an extended elliptical cross-section (where the long diameter is parallel to the surface of the silicon wafer), it is associated with the greatest mobile charge for a certain gate voltage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In nanotransistors, the optimal trade-off between performance and leakage currents can be achieved by engineering the device structures. In our previous publications [3], [4], we demonstrated that the crosssectional shape of the nanowires has a strong impact on the gate capacitance and the mobile charge in the NWTs. In particular, the NWT with <110> channel orientation and elongated elliptical cross-section with the long diameter parallel to the silicon wafer surface has the highest mobile charge for a given gate voltage [4].…”
mentioning
confidence: 85%